Assessment of methane and carbon dioxide emissions in two sub‐basins of a small acidic bog lake artificially divided 30 years ago. (10th September 2018) - Sepulveda‐Jauregui, Armando; Martinez‐Cruz, Karla; Lau, Maximilian; Casper, Peter
Abstract: Although lakes are important sources of methane (CH4 ) and carbon dioxide (CO2 ) to the atmosphere contributing to global warming, their CH4 and CO2 emissions are rarely assessed. In particular, increasing inputs of terrestrial dissolved organic carbon (DOC) may affect gas dynamics and alter seasonal changes in gas production. Here, we analysed variations in CH4 and CO2 dynamics in sub‐basins of an acidic bog lake, which was artificially divided into four quarters three decades ago, leading to divergence in water chemistry and biology. In the divided lake, only the south‐west basin (SW) received DOC inputs from an adjacent peat bog, while the north‐east basin (NE) was hydrologically disconnected. A year‐long determination of CH4 and CO2 production and emission patterns in the two contrasting basins exposed the indirect mechanisms by which DOC supply exercised control on greenhouse gas dynamics in this shallow lake. In both basins, dissolved CH4 was negatively correlated with dissolved oxygen (O2 ) through the water column, suggesting that aerobic methanotrophy is an important regulator of CH4 emissions in this lake. In contrast, the amount of CO2 stored in oxic and anoxic layers was not significantly different between the basins, suggesting that O2 is not the most important driver of dissolved CO2 . Estimated total CH4 and CO2 emissions were 2.1 and 1.7 times lower in the NE basin than in the SW basin, with major CH4 and CO2 emissions occurring during the fall turnover. The differences in CH4 and CO2 emissions suggest that the hydro‐physical properties, namely seasonal temperature, the duration of stratification and O2 availability, are the main drivers of CH4 and CO2 emissions to the atmosphere from small shallow lakes under the influence of DOC inputs under global warming pressure.